Parody, Controversy, Commercial Opportunity: Samuel Foote’s The Minor (1760) and Its Reception - Pierre Labrune (Sillages Critiques)
This article studies Samuel Foote’s comedy The Minor, created in 1760, and the controversy it provoked. As Foote’s play satirizes George Whitefield and his preaching, its legality was debated. The use of scriptural quotations by ridiculous characters was criticized as Methodists argued that religion itself was being ridiculed. Foote, however, constantly defended his right to lampoon hypocrites, and his play was a real success. Moreover, a new fashion for Anti-Methodist publications originated in the scandal surrounding The Minor, thus undermining the attempts to censor the play.